Impacts of banks’ financial performance before and during covid-19 period: a study of domestic Islamic banks in Malaysia - Chai, Phooi Yee; Ong, Xin Yi; Soon, Yong Kai; Tan, Jie Hong; Yoan, Sook Mun (2022)
This research project is to compare the performance of Malaysian Domestic Islamic Banks before and during the COVID-19 period. Besides, 11 Malaysia domestic Islamic Banks were chosen as the sample size, namely Affin Islamic Bank Berhad, Alliance Islamic Bank Berhad, AmBank Islamic Berhad, Bank Islam Malaysia Berhad, Bank Muamalat Malaysia Berhad, CIMB Islamic Bank Berhad, Hong Leong Islamic Bank Berhad, Maybank Islamic Berhad, MBSB Bank Berhad, Public Islamic Bank Berhad, and RHB Islamic Bank Berhad. External independent variable included in this study is gross domestic product (GDP), while internal independent variables included capital adequacy (CA), moratorium (MORA), and bank liquidity (BKLQ), whereas the dependent variable refers to return on assets (ROA). Furthermore, secondary data were collected for this study in quarterly basis from Bank Negara Malaysia (BNM) and quarterly financial report of each Islamic Banks. Random Effects Model (REM) is preferable in this study. The result of study shows that all the independent variables are significant to impact Islamic Banks’ profitability before COVID-19 period while GDP is the only significant variable that affect the performance of Islamic Banks during COVID-19 period.